A CRISE CAPITALISTA, O AVANÇO DA DIREITA NO CONTINENTE LATINO-AMERICANO, E OS DESAFIOS PARA A RESISTÊNCIA - Joana A Coutinho (Universidade Federal do Maranhão, 2020)
This article is the result of the presentation of a coordinated table at Joinpp 2019, whose theme was civilization or barbarism. It represents the set of presentations and, therefore, a summary of the discussions held at that time, and justifies an article with five authors. The advance of the right with new forms of organization, which culminates with the election of Jair Bolsonaro, as is the case in Brazil and the challenges for social movements, political parties, in this panorama.